The Influence of Self-Efficacy on Learning Motivation and Learning Achievement in Class V of SD Negeri 006 Petani Pelalawan Regency - Astri, Kharisma; Ain, Siti Quratul Ain (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research analyzes data in the form of numerical values with improved methodology using quantitative methodology. The research was conducted at Farmer School 006, Bunut District, Pelalawan Regency. Once the project has been vetted, which is scheduled to begin in July and August 2024, this study will be conducted. The population in this study were all fifth grade students at SD Negeri 006 Tantani, totaling 44 students in Bunut District, Pelalawan Regency. Research findings show that the self-efficacy variable has a large and good influence on student learning achievement. In other words, learning achievement increases along with student self-efficacy; On the contrary, learning achievement decreases along with student self-efficacy. This statement is supported by analysis findings which show a result of 20.5% with a significance value of 0.000<0.05 and a calculated f of 0.849. It is hoped that based on the theory used, future researchers will be able to investigate the impact of self-efficacy on additional factors or supporting data.